Biochemical characteristics and calcium and PTH levels of patients with high normal and elevated serum 25(OH)D levels in Turkey: DeVIT-TOX survey - Pekkolay, Zafer; Yavuz, Dilek Gogas; Saygili, Emre Sedar; Degertekin, Ceyla Konca; Topaloglu, Omercan; Onder, Cagatay Emir; Tuzcu, Alpaslan Kemal (Springer London Ltd, 2021)
A Summary Vitamin D intake over the recommended dose is usually associated with high serum 25(OH)D levels and generally not associated with symptoms of hypercalcemia. High doses of cholecalciferol need to be avoided to protect against vitamin D toxicity and related complications. Strict adherence to the clinical guidelines for treating vitamin D deficiency can ensure safe and effective treatment. Purpose We observed a tendency to use high doses of cholecalciferol for vitamin D deficiency treatment or vitamin D supplementation. We aimed to determine the biochemical characteristics of patients with high normal and elevated serum 25(OH)D levels. Methods An online invitation was sent to all tertiary endocrinology clinics in Turkey to complete an online retrospective survey (DeVIT-TOX Survey) for patients diagnosed with high serum 25(OH)D levels (> 88 ng/mL) between January 2019 and December 2019. The patients were evaluated according to the presence of signs and symptoms of hypercalcemia and doses of vitamin D intake, evaluated into the following three groups according to their 25(OH)D levels: group 1, > 150 ng/mL; group 2, 149-100 ng/mL; and group 3, 99-88 ng/mL. Results A total of 253 patients were included in the final analysis (female/male: 215/38; mean age, 51.5 +/- 15.6 years). The average serum 25(OH)D level was 119.9 +/- 33 (range, 88-455) ng/mL, and the average serum calcium level was 9.8 +/- 0.7 (range, 8.1-13.1) mg/dL. Most (n = 201; 75.4%) patients were asymptomatic despite having high serum 25(OH)D and calcium levels. The serum 25(OH)D level was significantly higher in the symptomatic groups than in the asymptomatic groups (138.6 +/- 64 ng/mL vs. 117.7 +/- 31 ng/mL, p < 0.05). The most common cause (73.5%) associated with high serum 25(OH) D levels was the inappropriate prescription of a high dose of oral vitamin D (600.000-1.500.000 IU) for treating vitamin D deficiency/insufficiency in a short time (1-3 months). The cut-off value of 25 (OH) D level in patients with hypercalcemia was found to be 89 ng/mL [median 116.5 (89-216)]. Conclusions High dose of vitamin D intake is associated with a high serum 25 OH D level, without symptoms of hypercalcemia. Inappropriate prescription of vitamin D is the primary cause for elevated 25(OH) D levels and related hypercalcemia. Hypercalcemia may not be observed in every patient at very high 25(OH) D levels. Adherence to the recommendation of guidelines is essential to ensure safe and effective treatment of vitamin D deficiency.
Keywords: Vitamin D toxicity; 25-OH vitamin D; Hypercalcemia; Cholecalciferol